Clinical Characteristics of Infective Endocarditis in Children. Issue 5 (May 2019) - Kelchtermans, Jelte; Grossar, Lorenz; Eyskens, Benedicte; Cools, Bjorn; Roggen, Mieke; Boshoff, Derize; Louw, Jacoba; Frerich, Stefan; Veloso, Tiago Rafael; Claes, Jorien; Ditkowski, Bartosz; Rega, Filip; et al.
Abstract : Background: Infective endocarditis (IE) remains a diagnostic and therapeutic challenge associated with high morbidity and mortality. We evaluated the microbial profile and clinical manifestation of IE in children. Methods: A retrospective study examining pediatric IE cases treated between 2000 and 2017 at the Department of Pediatric Cardiology, KU Leuven, was conducted. Clinical presentation, treatment, complications, outcome of IE, underlying microorganisms and congenital heart defects were reviewed. Results: Fifty-three patients were diagnosed with IE. Overall, 19 patients (36%) required cardiac surgery. Seven patients (13%) died. Eighty-seven percent of patients had an underlying congenital cardiac defect. Eighteen (34%) children presented with prosthetic graft IE. A causative organism was found in 49 (92%) cases: viridans group streptococci were identified in 17 (32%), Staphylococcus aureus in 13 (25%) and coagulase-negative staphylococci in 11 (20%) children. Community-acquired (CA) IE increased significantly from 8 (33%) cases in 2000–2007 to 20 (74%) cases in 2008–2017 ( P < 0.01). Even with viridans streptococci being significantly more prevalent in the CA group ( P < 0.01), we did not observe an increase of streptococcal IE from 2008 to 2017. Seventeen (32%) patients presented with hospital-acquired IE during the first year of life with 14 (82%) children after surgery and a prevalence of coagulase-negative staphylococci (53%). Conclusions: The incidence of pediatric IE was similar over the investigated time period with a shift toward CA IE. Streptococci and staphylococci accounted for the majority of cases in both periods. Awareness of IE and its prevention is crucial in patients after implantation of prosthetic grafts.